PEMBERDAYAAN ANAK PUTUS SEKOLAH MELALUI OPTIMALISASI PKBM DI DESA BATU BERIGA - Fitri Apriani; Yurdayanti Yurdayanti (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
One of the problems in Batu Beriga Village is the problem of education. From the educational statistics for the Batu Beriga village community, the highest number of graduates of 517 was elementary school graduates, then 342 junior high school graduates and 280 high school graduates. And also data on dropouts in Batu Beriga village were 10 elementary school dropouts, 15 junior high school dropouts, and 15 people dropped out of high school. The twelve-year compulsory education program with the policies and programs of the Student Operational Assistance (BOS) and the Smart Indonesia Program (PIP) set by the government. Therefore, knowledge about the importance of education and PKBM will be given to out-of-school children in Batu Beriga village with an Inspirational Talk Show on Strengthening Educational Motivation for Dropout Children to collect data on children's interest in participating in PKBM, and registering children to take part in PKBM. The method used is the counseling method with the preparation and licensing stages, the implementation stage, and the evaluation stage. Overall, this community service activity went very well and was conducive. All participants who attended calmly followed the whole activity. Until the completion of the presentation of the material by the speaker, all participants listened carefully. There were 7 school dropouts who enrolled in PKBM.